2005
DOI: 10.1679/aohc.68.259
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of the neurokinin 1 receptor in rat dental pulp

Abstract: The dentin-pulp complex is a peripheral end-organ supplied by dense sensory nerve fibers. Substance P, a representative neuropeptide widely distributed in the dental pulp, has been reported to play roles in pain transmission and the amplification of inflammation. We analyzed here the expression of the neurokinin 1 (NK1) receptor, preferentially activated by substance P, using immunocytochemistry in rat dental pulp at both the light and electron microscopic levels. Conspicuous NK1 receptor immunoreactivity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…NK1 and NK2 receptors have been reported in odontoblast as well as in enamel forming cells (ameloblasts). As expected NK1 receptor is abundantly present on capillaries and smaller blood vessels, and both NK1 and NK2 receptors are densely distributed on the capillary plexus subjacent to dentin [27]. …”
Section: Sp and Its Receptors In Dental Pulpmentioning
confidence: 53%
See 3 more Smart Citations
“…NK1 and NK2 receptors have been reported in odontoblast as well as in enamel forming cells (ameloblasts). As expected NK1 receptor is abundantly present on capillaries and smaller blood vessels, and both NK1 and NK2 receptors are densely distributed on the capillary plexus subjacent to dentin [27]. …”
Section: Sp and Its Receptors In Dental Pulpmentioning
confidence: 53%
“…A few studies have characterized the presence of NK receptors in rodent and human teeth [27, 28]. Animal studies identified the expression pattern of the tachykinin receptors NK1, NK2, and NK3 in different types of hard tissue cells, epithelial cells, fibroblasts, endothelium, and blood vessel walls in teeth and supporting oral tissues.…”
Section: Sp and Its Receptors In Dental Pulpmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be speculated that NK1 is the receptor most involved in physiological conditions, while NK1 and NK2 become involved in pathological conditions because of the higher SP concentrations [37]. Kido et al [38], 2005, using immunocytochemical studies in rat dental pulp, reported that NK1 receptors were present in odontoblasts and ameloblasts and were abundant on capillaries and smaller blood vessels, and both NK1 and NK2 receptors were found on the capillary plexus subjacent to the dentin. Substance P receptors have also been reported in human pulp tissue, although the methods used for their evaluation, the radioreceptor assay, did not allow investigators to measure which type of receptor (NK1, NK2, or NK3) was primarily present [39].…”
Section: Molecular Basis Of Pulpal Inflammationmentioning
confidence: 99%